FAKTOR EKONOMI DAN POLITIK DALAM FORMULASI STRATEGI PERTAHANAN: PERSPEKTIF NEGARA BRICS - Aldi Himawan; Toriq Furqon Al-Mujaddid; Suwito, Suwito (CV. AFDIFAL MAJU BERKAH, 2024)
This narrative provides a comprehensive analysis of the economic, political, and diplomatic factors influencing defense strategy formulation within the BRICS (Brazil, Russia, India, China, South Africa) context. Drawing on a wide range of sources, the narrative explores the historical evolution and recent shifts in BRICS defense strategies, highlighting the diverse approaches of member nations. The research adopts a qualitative descriptive approach, systematically gathering secondary data from academic journals, governmental reports, and reputable websites. The analysis focuses on the interplay between economic conditions, political dynamics, and defense strategy formulation in BRICS nations, providing nuanced insights into how these factors shape defense policies. It examines the influence of economic dependency on defense policies, emphasizing the role of economic stability in sustaining robust defense capabilities. Additionally, the narrative delves into the impact of political systems and leadership dynamics on defense strategy formulation, as well as the significance of diplomatic relations and security considerations. The findings underscore the complex interplay between economic, political, and defense factors within the BRICS framework, with implications for regional stability and resilience. The study finds that economic dependency is a pivotal factor in shaping BRICS defense strategies, with economic stability underpinning the capacity for robust defense capabilities. Political systems and leadership dynamics also play a crucial role, with centralized systems facilitating assertiveness and democratic frameworks emphasizing consensus-building. Diplomatic relations and security cooperation are integral to these strategies, highlighting the importance of strategic collaboration in addressing shared security challenges. The expansion of BRICS introduces new dynamics, particularly in energy investment and trade, requiring adaptive strategies to maintain stability and resilience. Finally, the narrative suggests future research directions to further explore these dynamics and enrich our understanding of BRICS defense strategies in the evolving global security landscape.